Influencing factors for Pisa syndrome in patients with Parkinson's disease - HUANG Gen; CAO Huimin; NIE Xiangtao; YU Gang (陆军军医大学学报, 2023)
Objective To observe the clinical characteristics of Parkinson's disease (PD) patients complicated with Pisa syndrome (PS), and to explore the influencing factors for PS occurrence in the PD patients. Methods A nested case-control study was conducted on 222 patients continuously diagnosed with PD but not with lateral spinal flexion admitted in our department from September 2020 to December 2020. After 2 years of follow-up, 26 PD patients complicated with PS were assigned into observation group, and 98 sex- and age-matched PD patients without PS complication were assigned into control group in a ratio of 1 ∶4. Their demographic and clinical data were collected, and the relevant scales and questionnaires were performed, including Hoehn and Yahr (H-Y) Staging Scale, Parkinson's Disease Questionnaire-8 (PDQ-8), Unified Parkinson's Disease Rating Scale (UPDRS), Visual Analogue Scale (VAS), Montreal Cognitive Assessment Scale (MoCA), Hamilton Anxiety Scale (HAMA) and Hamilton Depression Scale (HAMD). Results There were significant differences between the observation group and the control group in the course of the disease, equivalent daily dose of levodopa, drug adjustment, repeated falls within half a year, H-Y stage, UPDRS-Ⅲ score, score of axial symptoms, rigidity score, VAS score, PDQ-8 score, HAMA score, HAMD score and MoCA score (P < 0.05). Multivariate logistic regression analysis showed that the occurrence of PS was closely correlated with score of axial symptoms (OR=1.402, 95%CI=1.050~1.872, P=0.022), rigidity score (OR=1.429, 95%CI: 1.053~1.937, P=0.022) and VAS score (OR=1.772, 95%CI: 1.089~2.883, P=0.021). ROC curve analysis indicated that the AUC value of score of axial symptoms, rigidity score and VAS score was 0.899, 0.835 and 0.827, with a Youden index of 0.681, 0.558 and 0.488, respectively. Conclusion The severities of axial symptoms, rigidity and low back pain in PD patients are closely associated with the occurrence of PS.